Thymosin β(10) Expression Driven by the Human TERT Promoter Induces Ovarian Cancer-Specific Apoptosis through ROS Production - Kim, Young-Chae (Public Library of Science, 2012)
Thymosin β(10) (Tβ(10)) regulates actin dynamics as a cytoplasm G-actin sequestering protein. Previously, we have shown that Tβ(10) diminishes tumor growth, angiogenesis, and proliferation by disrupting actin and by inhibiting Ras. However, little is known about its mechanism of action and biological function. In the present study, we establish a new gene therapy model using a genetically modified adenovirus, referred to as Ad.TERT.Tβ(10), that can overexpress the Tβ(10) gene in cancer cells. This was accomplished by replacing the native Tβ(10) gene promoter with the human TERT promoter in Ad.TERT.Tβ(10). We investigated the cancer suppression activity of Tβ(10) and found that Ad.TERT.Tβ(10) strikingly induced cancer-specific expression of Tβ(10) as well as apoptosis in a co-culture model of human primary ovarian cancer cells and normal fibroblasts. Additionally, Ad.TERT.Tβ(10) decreased mitochondrial membrane potential and increased reactive oxygen species (ROS) production. These effects were amplified by co-treatment with anticancer drugs, such as paclitaxel and cisplatin. These findings indicate that the rise in ROS production due to actin disruption by Tβ(10) overexpression increases apoptosis of human ovarian cancer cells. Indeed, the cancer-specific overexpression of Tβ(10) by Ad.TERT.Tβ(10) could be a valuable anti-cancer therapeutic for the treatment of ovarian cancer without toxicity to normal cells.